THE KNOWLEDGE EVOLUTION OF AMERICAN PUBLIC ADMINISTRATION: A CONCEPT, CONTENT, AND HISTORICAL ANALYSIS OF INTRODUCTORY TEXTBOOKS - (:unkn) unknown (My University, 2011)
Disciplinary knowledge is what scholars pursue in their fields, what practitioners execute in practice, and what students learn for future careers. Despite various appraisals of the nature of the study (Waldo 2007[1948]; 1955; Hale 1988; Stillman 1999a; Raadschelders 1999; 2000; 2004; 2005; 2008; 2011), the knowledge of public administration (PA) has not been chronologically and systematically investigated. The purpose of this research is to examine the nature and trends of PA knowledge in the US. Using a systematic method combining concept, content, and historical analyses, three essential constituents of disciplinary knowledge are analyzed: concepts, topics, and perspectives, as they appear in introductory textbooks published from the 1920s to the 2000s. The findings are as follows: 1) the various ways in which PA has been defined indicate that the textbook authors grasp the reality of PA differently; 2) conceptual modification and transformation are intended to resolve conceptual discrepancy between a PA concept and its meaning, on the one hand, and its empirical object, on the other; 3) the treatment of PA topics and the development of their subtopics vary across time and among authors; and 4) PA perspectives reflect the authors' pedagogical intentions and scholarly standpoints. A surprising finding is that a clear distinction is visible between the early textbooks before the 1970s and the later ones, in which the contents and conceptualization seemingly become standardized. This research concludes that the knowledge of American PA has evolved by means of the attributes of PA, conceptual changes, topic variation and development, and different perspectives. Finally, this research suggests two future studies: an externalist analysis of knowledge development and an analysis of the pedagogical contents of introductory textbooks.
Keywords: Public administration--Study and teaching--United States--History; Public administration--United States--Textbooks--History